Standardisation and evaluation of physico chemical properties of jackfruit based bio-yoghurts - Remya PR, Sharon CL; Rammya Molu K (Indian Journal of Dairy Science, 2024)
Jackfruit, the state fruit of Kerala, is often regarded as a wonder fruit due to its nutrient profile, nutraceutical and health benefits and the immense scope for value addition. However it is mostly underutilized due to lack of knowledge and technical facilities. It can be better utilised, if consumer acceptable, simple as well as nutritious products are prepared out of the fruit. The growing demand for “healthy food” is stimulating the innovation and development of new products nationally and internationally. Yoghurt, a milk based product, is a simple, healthy and nutritious food which offers high amounts of protein, carbohydrates and fat. The added value of yoghurt over milk lies on the presence of beneficial bacteria as well as certain bioactive components. The study was aimed at developing jackfruit based bio-yoghurts and to evaluate its physico- chemical properties. Lactobacillus acidophilus was used as the probiotic organism in this study. Hence in this study, yoghurts were prepared by incorporating varying proportions of blanched jackfruit pulp (10%, 20% and 30%) along with equal volumes of homogenized milk. Both koozha and varikka variety of jackfruits were used for the preparation of bio-yoghurts. The jackfruit bulbs were steam blanched for five minutes and pulped to prepare the bio-yoghurt. Plain yoghurt served as the control. The prepared bio-yoghurts were organoleptically evaluated using a 9 point hedonic scale with a panel of 15 judges. The selection of best sample was done on the basis of Kendall’s coefficient of concordance. Among the fruit based bio-yoghurts, the yoghurt with 30% jackfruit pulp scored maximum for the sensory attributes. Physico-chemical parameters like synerisis, water holding capacity, curd tension, viscosity, pH, moisture, fat and protein of the bio-yoghurts were determined.